(untitled) (Research, Society and Development, 2021)
Objective: To describe the epidemiological characteristics of dengue in the State of Mato Grosso, Brazil, from 2001 to 2018.Methods: Data were obtained from the Informatics Department of the Unified Health System (DATASUS) for analyzes of lethality, incidence and hospitalization. Results: In the state of Mato Grosso there were 292,756 notifications and 256 deaths in the period studied. The peak of incidence and lethality was in 2009 (male 1544.1; female 1960.3; male 268.1; female 107.2 cases / 100 thousand inhabitants), respectively. However, the hospital admission rate (male 156.4 / 100 thousand inhabitants; female 178.1 / 100 thousand inhabitants) was in 2010. The peak incidence rate in the age groups was in 2009, in which children (<1 year ) had a higher incidence rate, with 2156.8 / 100 thousand inhabitants this year. Then the teenagers (10 to 19 years old) with 2003.4 / 100 thousand inhabitants); adults (20 to 59 years old; 1740.4 / 100 thousand inhabitants); children (1 to 9 years; 1653.8 / 100 thousand inhabitants) and the lowest rates were among the elderly (> 60 years; 1257.1 / 100 thousand inhabitants). The highest lethality rate was in the elderly 435.9 / 100 thousand inhabitants, then in children (<1 year; 335.2 / 100 thousand inhabitants); in children (1 to 9 years; 86.9 / 100 thousand inhabitants); in adults 54/100 thousand inhabitants and; the lowest among adolescents with 40.3 / 100 thousand inhabitants. Conclusion: Dengue showed epidemic peaks with high incidence rates. The female sex gets sick and hospitalizes more than the male, but the male has a higher lethality. Adults become more ill, however, lethality is higher in the elderly.